Pengaruh Penerapan E-Billing dan E-SPT terhadap Kepatuhan Wajib Pajak di Kota Padang - Seftrini Visrizamet; Aldri Frinaldi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
This study uses a method called a quantitative survey. It uses a Likert scale questionnaire to collect quantitative data that has been tested for validity and reliability. The people in this study are taxpayers who signed up at the Pratama Tax Service Office in Padang as E-Billing Taxpayers. Satu as many as 29,372 Taxpayers, this study used the Slovin formula to get 100 respondents (with a 10% error rate) and then used multiple linear regression to look at the data. In this study, it can be seen that there is a positive and significant effect between the independent variable (E-Billing) and the dependent variable (taxpayer compliance in the city of Padang), which has been tested with a significance of 0.000, less than 0.05, and the effect of the application of E-SPT on the dependent variable (taxpayer compliance in the city of Padang).